Effect of Some Navels on Properties of Cotton/Nylon66 Blend (1 : 1) Rotor Spun Yarn and Wrapper Formation: A Comparison between Rotor and Ring Spun Yarn. (12th March 2013) - Yadollah Roudbari, Babak; Eskandarnejad, Safdar
Abstract : Use of nylon/cotton blend yarn in military uniform is common and due to advantages in its fabric in comparison to 100% cotton fabrics, capabilities of military uniforms have been improved. In this study the effects of navel type on properties of (50%-50%) nylon/cotton blend yarn and wrapper formation were investigated and compared with similar ring spun yarn. Rotor spun yarn was produced on a single head laboratory rotor spinning machine with four navels (smooth, spiral, 3 grooved, and 4 grooved) and ring yarn was produced on a zinser 319 ring spinning machine. Test result showed that navel type has a significant effect on yarn strength and strength of smooth navel yarn was maximum. Elongation of a 100% cotton rotor spun yarn is more than similar ring yarn, but it was not observed in cotton/nylon blend. Yarn irregularity and imperfections varied significantly with navel type and for rotor yarns were more than the ring yarn. Navel type had significant effect on yarn hairiness but it didnot have an effect on yarn abrasion significantly.